Twenty amino acids at the C-terminus of PA-X are associated with increased influenza A virus replication and pathogenicity - Gao, Huijie; Sun, Yipeng; Liu, Xiufan; Sun, Honglei; Hu, Jiao; Wang, Jinliang; Lin, Yang; Chang, Kin-Chow; Wang, Yu; Qi, Lu; Pu, Juan; Xiong, Xin; et al. (Microbiology Society, 2015)
The PA-X protein, arising from ribosomal frameshift during PA translation, was recently discovered in influenza A virus (IAV). The C-terminal domain ‘X’ of PA-X proteins in IAVs can be classified as full-length (61 aa) or truncated (41 aa). In the main, avian influenza viruses express full-length PA-X proteins, whilst 2009 pandemic H1N1 (pH1N1) influenza viruses harbour truncated PA proteins. The truncated form lacks aa 232–252 of the full-length PA-X protein. The significance of PA-X length in virus function remains unclear. To address this issue, we constructed a set of contemporary influenza viruses (pH1N1, avian H5N1 and H9N2) with full and truncated PA-X by reverse genetics to compare their replication and host pathogenicity. All full-length PA-X viruses in human A549 cells conferred 10- to 100-fold increase in viral replication and 5–8 % increase in apoptosis relative to corresponding truncated PA-X viruses. Full-length PA-X viruses were more virulent and caused more severe inflammatory responses in mice. Furthermore, aa 233–252 at the C terminus of PA-X strongly suppressed co-transfected gene expression by ∼50 %, suggesting that these terminal 20 aa could play a role in enhancing viral replication and contribute to virulence.